Sustained Effects of High-Intensity Interval Exercise and Moderate-Intensity Continuous Exercise on Inhibitory Control - Tian, Shudong (Int J Environ Res Public Health, 2021)
This study examined the immediate and sustained effects of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) bouts on inhibitory control in young adults. Participants (n = 41) engaged in (1) a session of HIIE, involving 10 one-minute runs on a treadmill at an intensity targeting 85–90% HR(max) interspersed with self-paced walking at 60% HR(max); (2) a session of MICE, involving a 20 min run on a treadmill at an intensity of 60–70% HR(max); and (3) a control session, involving 24 min of resting on separate days in a counterbalanced order. Using a flanker task, inhibitory control was assessed before the intervention (t(0)), immediately after the session (t(1)), and then at 30 min (t(2)), 60 min (t(3)), and 90 min (t(4)) after the session. During the flanker task, the response time (RT) for incongruent trials immediately after HIIE was significantly shortened compared to that before exercise. This shortened RT was sustained for 90 min post-exercise during recovery from HIIE. Interference scores of RT were also reduced after HIIE, benefitting inhibitory control, and were maintained for 90 min post-exercise. Reduced accuracy interference scores were recorded following HIIE compared to the control session. Improvements in inhibitory control elicited by HIIE were sustained for at least 90 min post-exercise. In contrast, an improvement in inhibitory control was not observed during the MICE session. HIIE might represent a time-efficient approach for enhancing inhibitory control.